Legal Aspects of Artificial Intelligence on Automated Decision-Making in Indonesia - Denindah Olivia (University of Jember, 2020)
This paper analyzes the importance of Indonesia's comprehensive legal framework on automated decision-making empowered by Artificial Intelligence, comparing it to the European Union, the United States, and China. Specifically, this paper inquires about the status quo of the legal protection of automated decision-making In Indonesia. The analysis highlights profiling in an automated decision-making system with the following discussion about personal data protection. In this context, the European Union's member states set out the General Data Protection Regulation (GDPR) that prohibits automated decision-making to a certain extent. In the United States, the practice of automated decision-making is rather usual. Simultaneously, China takes an exceptional measure instead and develops this automation through a social credit system. The analysis concludes that Indonesia has weak legal protection towards personal data and profiling, which later becomes the basis in facilitating automated decision-making. The provision of automated decision-making and profiling is the absolute bare minimum to Indonesia's Personal Data Protection Bill due to insufficient legal certainty. In the end, it is paramount for lawmakers to consider a comprehensive regulation on automated decision-making by adopting the European Union's GDPR framework. KEYWORDS: Artificial Intelligence, Automated Decision-Making, Personal Data Protection.